PENGARUH MODEL PEMBELAJARAN PROBLEM BASEAD LEARNING (PBL) TERHADAP HASIL BELAJAR IPAS KELAS V SD NEGERI 05 SALIDO KECIL - Oktavia, Windiana; Sari, Nauli Tama (STKIP Pesisir Selatan, 2025)
PBL is a student-centered learning model oriented towards authentic problem solving. Through PBL stages such as problem orientation, data collection, group discussions, and presentations, students are encouraged to think critically, creatively, and collaboratively. PBL is a student-centered learning model oriented towards authentic problem solving. Through PBL stages such as problem orientation, data collection, group discussions, and presentations, students are encouraged to think critically, creatively, and collaboratively.This study aims to determine the effect of the Problem Based Learning (PBL) learning model on the learning outcomes of Natural and Social Sciences (IPAS) in fifth-grade students at SD Negeri 05 Salido Kecil. This research is motivated by the low learning outcomes of students due to the lack of active involvement in the learning process. This study uses a quantitative approach with an experimental method of one group pretest-posttest design. The sample in this study amounted to 18 fifth-grade students. The instruments used were multiple-choice tests, observation sheets, and documentation. Data analysis used descriptive statistics and t-test. The results showed a significant increase in learning outcomes. The average pretest score of 66 increased to 80 in the posttest. The t-value of 5.833 is greater than the t-table of 1.713 with a significance of 0.052. This indicates that the PBL model has a positive effect on IPAS learning outcomes.